2021
DOI: 10.1002/alz.12283
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic and prognostic capabilities of plasma biomarkers in Alzheimer's disease

Abstract: Introduction This study investigated the diagnostic and disease‐monitoring potential of plasma biomarkers in mild cognitive impairment (MCI) and Alzheimer's disease (AD) dementia and cognitively unimpaired (CU) individuals. Methods Plasma was analyzed using Simoa assays from 99 CU, 107 MCI, and 103 AD dementia participants. Results Phosphorylated‐tau181 (P‐tau181), neurofilament light, amyloid‐β (Aβ42/40), Total‐tau and Glial fibrillary acidic protein were altered in AD dementia but P‐tau181 significantly outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
202
2
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 236 publications
(226 citation statements)
references
References 63 publications
20
202
2
2
Order By: Relevance
“…The high analytical sensitivity (< 1 pg/mL) of the single-molecule array (Simoa) allows for predilution of samples that may reduce matrix effects. Subsequently, using this technique for Aβ [63], a significantly lower plasma Aβ42/40 ratio was found in both MCI and AD cases as compared with controls [25,64]. Furthermore, marginally improved associations were found with CSF Aβ and amyloid PET [64].…”
Section: Phase 1: Primary Aimmentioning
confidence: 94%
See 3 more Smart Citations
“…The high analytical sensitivity (< 1 pg/mL) of the single-molecule array (Simoa) allows for predilution of samples that may reduce matrix effects. Subsequently, using this technique for Aβ [63], a significantly lower plasma Aβ42/40 ratio was found in both MCI and AD cases as compared with controls [25,64]. Furthermore, marginally improved associations were found with CSF Aβ and amyloid PET [64].…”
Section: Phase 1: Primary Aimmentioning
confidence: 94%
“…For IPMS studies, the AUC for Aβ42 ranges from 72-87% [67,87], between 80-97% for Aβ42/Aβ40 [66,67,86,87] and between 82-97% for the APP669-711/Aβ42 [67,87]. In contrast, accuracies of between 60-64% and 62-68% have been reported for the commercially available Simoa assays [25,64,103], although higher AUCs were achieved for a modified version of the Simoa assay which utilized differing antibodies [102]. Plasma Aβ42/Aβ40 measured by the fully automated Elecsys assay predicts Aβ status with an accuracy > 80% [85].…”
Section: Phase 2: Secondary Aimmentioning
confidence: 99%
See 2 more Smart Citations
“…These latest studies have investigated the dynamic changes of plasma ptau181 across the AD spectrum [100] and the relationship between polygenic risk scores for AD and plasma ptau181 [101]. They have also compared performance of ptau181 with other biomarkers in AD and MCI prediction [102] or amyloid PET status prediction [103]. In addition, ptau217 [104] and ptau231 (Ashton et al in press) have been reported recently to differentiate AD from other neurodegenerative disorders and be associated with tau pathology in the brain.…”
Section: Limitationsmentioning
confidence: 99%